Effect of PGPB (Plant Growth Promoting Bacteria) and NPK Fertiliser on The Growth of Tomato Plants (Solanum lycopersicum) Infected with Fusarium sp. - Suryanti, Erma; Chusniasih, Dewi; Arliani Nur Anisa, Hida; Anbar Istiadi, Khaerunissa; Restiati, Nawang; Anggria Sari, Dian (Biotropika: Journal of Tropical Biology, 2026)
The long-term use of NPK fertiliser harms the environment, therefore, the use of NPK fertiliser needs to be balanced with biological fertilisers. The biological fertiliser used was PGPB (Plant Growth-Promoting Bacteria) TNAP1, TNCP1, and ANAP1 isolated from pineapple plants. This study aimed to determine the antagonistic activity of TNAP1, TNCP1, and ANAP1 isolates, assess the viability oF PGPB bacteria in the carrier material (Biochar) during storage, and evaluate the effect of NPK and PGPB fertiliser combination on the growth of tomatoes (Solanum lycopersicum) infected with Fusarium sp. This study conducted antagonism tests between PGPB isolates, PGPB antagonism with Fusarium sp. in vitro, formulation of PGPB fertiliser on the carrier material, viability test of bacteria, Fusarium sp. infection in tomato plants, fertilisation, and observation. The observed growth parameters were plant height, number of leaves, number of flowers, number of fruits, and chlorophyll content. The results of this study showed that the three bacterial isolates had synergistic properties, the viability of PGPB bacteria was above 107 CFU/g and met the requirements of the Regulation of the Ministry of Agriculture No. 70 of 2011, and the P2 treatment with a combination of fertilisers (50% NPK + 50% PGPB) gave the best results for all growth parameters and did not differ significantly from the positive control.